The role of substance p in bovine pneumonia caused by Mannheimia haemolytica - Ragsdale, John (Kansas State University, 2010)
The bovine respiratory disease complex (BRDC) is a major concern for cattle producers in the United States and worldwide. One of the most costly and deadly components of BRDC is bovine pneumonic pasteurellosis (BPP) caused by Mannheimia haemolytica. The initial pulmonary inflammation associated with BPP is a characteristic serofibrinous exudation into the lung, which is believed to be induced by M. haemolytica virulence factors such as lipopolysaccharide (LPS) and leukotoxin (LKT) and host cytokines and chemokines such as tumor necrosis factor – α, interleukin – 1β, and interleukin – 8. However, these pulmonary changes often occur before virulence factors or cytokines are substantial components of the pulmonary microenvironment. Other proinflammatory molecules such as substance P (SP) may be involved in the pathogenesis of the peracute serofibrinous exudation of BPP. SP is an 11 amino acid long neuropeptide that is a neurotransmitter of pain that can be released from sensory nerves into tissues to cause neurogenic inflammation. Neurogenic inflammation is characterized by serofibrinous exudation and leukocyte activation. SP-like immunoreactivity was present in the airways, alveolar septa, macrophages, endothelium, and peribronchial nerves in both pneumonic and normal bovine lung; however, SP-like immunoreactivity was increased in pneumonic compared to normal bovine lung due to increased immunoreactivity in macrophages. SP and the combination of SP with histamine and LPS increased the permeability of a calf pulmonary arterial endothelial cell line to Evans blue dye labeled albumin by 12.34%, 13.57%, and 22.03%, respectively compared to a cell control. Similarly, SP and the combination of SP and histamine increased the monolayer permeability of a bovine adrenal gland capillary endothelium by 8.27% and 16.69% compared to a cell control. The increase in permeability was due to endothelial cell shape change and the formation of intercellular gaps rather than cell death. However, SP does not increase the surface expression of the β2 integrin CD18 (the M. haemolytica LKT receptor) on bovine neutrophils nor does it increase LKT-induced leukocytotoxicity of bovine peripheral blood leukocytes. These findings indicate that SP may be a contributor to BPP in association with other cytokines.
Keywords: Bovine; Pneumonia; Mannheimia haemolytica; Substance P; Agriculture, Animal Pathology (0476); Biology, Veterinary Science (0778)